Fostering Inclusive Rural Innovation : The Case of INCAGRO in Peru - Ramirez, Ana Francisca; De Nys, Erwin; Elizabeth Dasso, Maria (World Bank, Washington, DC, 2012)
Both women and indigenous peoples face key barriers that limit their capacity to access and benefit from development projects. In a country like Peru where women and indigenous peoples represent a large share of the rural poor, integrating proactive measures into project design is crucial to reach these populations. The Peru Agricultural Research and Extension Program (INCAGRO) gave great emphasis to designing financing instruments that will give equitable opportunities to indigenous peoples and women's organizations. The 'en breve' will describe how INCAGRO integrated indigenous peoples and women's organizations into its activities to strengthen the market for agricultural services.